Effectiveness of a Media Combination Based Learning Drifting Model on Basic Football Technical Skills - Mutaqin, Mohamad Misbah; Hernawan; Setiawan, Iwan (Gladi : Jurnal Ilmu Keolahragaan, 2026)
The learning model for dribbling based on a combination of media is here to update physical education learning in schools. By utilizing technological advances, the learning model through an animated video approach provides a significant approach to the learning process of high school and equivalent students. However, there are definitely challenges in each application, but the benefits provided are very clear, good or positive. In accordance with the needs of students in modern times. This research uses quantitative and qualitative approaches and uses the ADDIE model in Research & Development (R & D). Consisting of five stages, with a total sample of 175 students. From the results of the small group trial data analysis, the percentage was 80.09%, this achievement is included in the good category. For large group trials, the results were 81.025%, which is also included in the good category. This is reinforced by the results of the N-Gain Score, obtained at 64.23% with an average of 0.64. Proves that the model is included in the good classification and also explains the effective learning model used to improve the skills and active participation shown by high school students of the same level. Therefore, this model is highly recommended so that it can be implemented in the learning process in schools.